The emergent school through artistic practice, experience and subjectivity - Báez Cárdenas, Carlos Julio (Universidad Pedagógica y Tecnológica de Colombia, 2010)
In relation to schools, subjectivity is a concept that broadens existing visions of classroom experience, artistic practice and the role of the teacher in recognizing and acting with respect to students’ affective awareness. This article presents a discussion about the importance of artistic education in primary and secondary education institutions, focusing on three stages related to subjectivity, school communication channels, and art teachers’ reflections about artistic thinking. This article also emphasizes on the use of qualitative research as a fundamental tool in reasoned discussion about the school environment. We conclude by describing the loss of meaning experienced by the educational institution, caused by the failure of its communication mechanisms, which can be perceived by the general disinterest of its actors and the lack of incentives that enhance the sense of belonging and professional quality of its teachers.